Declarative agent languages and technologies VI : 6th International Workshop, DALT 2008, Estoril, Portugal, May 12, 2008, revised selected and invited papers - Baldoni, Matteo (Springer, 2017)
This volume constitutes the revised selected papers of the 6th International Workshop, DALT 2008, held as satellite workshop of AAMAS 2008, the 7th International Joint Conference on Autonomous Agents and Multiagent Systems, in Estoril, Portugal, on May 12, 2008. The 12 papers, presented together with 3 invited papers, were carefully reviewed and selected from 14 submissions. The workshop provided a discussion forum to both (i) support the transfer of declarative paradigms and techniques to the broader community of agent researchers and practitioners, and (ii) to bring the issue of designing complex agent systems to the attention of researchers working on declarative languages and technologies.